The Assessment of Substitution Through Event Studies - An Application to Supply-Side Substitution in Berlin's Rental Market - Tomaso Duso; Claus Michelsen; Maximilian Schaefer; Kevin D Tran (Journal of European Competition Law & Practice, 2022)
One key question that arises when assessing a supply-side theory is to what extent a firm that is not yet present in the market but has capabilities to repurpose its production capacity constitutes a competitive constraint to firms operating in the focal market. The main challenge for identifying and measuring the competitive effects of potential entrants on a focal market of interest is that entry does not occur randomly and that firms select the markets in which to enter. We propose exploiting policy interventions that affect entry decisions to alleviate such concerns. To exemplify our approach, we assess how regulations that limit the diffusion of Airbnb in Berlin, affects equilibrium supply and prices in the long-term rental market by repurposing short-term Airbnb rentals to the focal market. Our results suggest that there exists supply-side substitution between professional Airbnb hosts and the long-term rental market. Yet, the size of Airbnb apartments stock held by professional users is not such to constitute a true competitive constraint on the long-term rental market.
Keywords: 330